Caracterización clínica y estudio genético de una cohorte colombiana con trastorno del espectro autista idiopático (2020)
The autism spectrum disorder (ASD) is a complex disorder encompassing a broad phenotypic and genotypic variability. The twin concordance rate and a milder autism phenotype in relatives reflect a strong genetic component in the pathophysiology of ASD; nevertheless, the broad phenotypic variability of this disorder and the 60% of individuals who remain with unknown etiology suggest an interplay of several genetic factors. Aiming to promote a better knowledge of ASD, this doctoral thesis pursued four goals: to recognize the clinical heterogeneity of ASD in our population, to identify rare copy number variants (CNVs) previously associated with a neurodevelopmental disorders, to evaluated de novo protein truncating variants in haplonsufficient genes with brain expression and to evaluate the 5-HTTLPR polymorphism in our cohort likewise its frequency in the under-represented Latin American population. Our clinical analyses revealed that high functioning and regressive are ASD subtypes present in our population, and that the male was the most frequent sex affected in our cohort. We did not observe differences in severity or ASD subtypes according to gender, although intellectual disability was higher in women. Following a rigorous molecular analyses we identified five rare non-recurrent CNVs probably involved in the ASD etiology: one de novo deletion involving the haploinsufficient ARGLU1 and EFNB2 genes, one small inherited deletion involving part of DOCK4 gene, one inherited duplication involving NUP98, PGAP2 and RHOG as interesting genes, and two inherited duplications involving among other genes CREM and CUL2 in one variant and YWHAE and CRK in the second variant. A collaborative work between Andes University and the autism consortium sequencing from Mount Sinai also led us to perform a Family-based whole exome sequencing and to identify ASD candidate variants in 13 participants (13.8%), three disrupted genes were already known ASD risk genes (CHD8, ASH1L and SYNGAP1).